2019
DOI: 10.3390/lubricants7100088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Viscosity and Speed on Oil Cavitation Development in a Single Piston-Ring Lubricant Assembly

Abstract: A high-speed camera has been used to produce unique time-resolved images of high quality to describe the dynamics of the lubricant flow and cavitation characteristics in a sliding optical liner over a fixed single piston-ring lubricant assembly for three lubricants with different viscosities to establish their impact on cavitation formation and development. The images were obtained at two cranking speeds (or liner sliding velocity) of 300 rpm (0–0.36 m/s) and 600 rpm (0–0.72 m/s), at a lubricant temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(19 reference statements)
3
8
0
Order By: Relevance
“…As a final conclusion, and in combination with previous findings in Nouri et al (2019), the results showed that viscosity plays a major role in the breakup process of the cavities so that lubricants with higher viscosity resist more cavity disintegration. Composition of lubricants will also play a major role in cavities formation, development and collapse and also related information on lubricants' properties, with the major one being their surface tension, which plays a major role in cavities' breakup.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As a final conclusion, and in combination with previous findings in Nouri et al (2019), the results showed that viscosity plays a major role in the breakup process of the cavities so that lubricants with higher viscosity resist more cavity disintegration. Composition of lubricants will also play a major role in cavities formation, development and collapse and also related information on lubricants' properties, with the major one being their surface tension, which plays a major role in cavities' breakup.…”
Section: Discussionsupporting
confidence: 85%
“…As a final conclusion, and in combination with previous findings in Nouri et al. (2019), the results showed that viscosity plays a major role in the breakup process of the cavities so that lubricants with higher viscosity resist more cavity disintegration.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Viscosity is a measurable physical property that can translate information about the liquid's hydration, solvation, the shape of the infused particles, and the forces acting between the particles [64]. It can also be defined as the internal resistance that a fluid has to flow.…”
Section: Viscositymentioning
confidence: 99%
“…Extensive reviews of all previous works in piston-ring lubricant assembly have been given by Vasilakos, 4 Ostovar, 12 Dhunput, 13 who also used different techniques like high-speed visualisation, LIF, capacitance and pressure transducers to visualise the oil film flow and cavitation formation, to measure the oil film thickness, the friction and the pressure distribution within the contact point between the rings and the liner. The recent experimental work 14 used the high-speed visualisation and a specially written MATLAB programme to quantify the effect of speed and lubricant viscosity on cavitation development. They showed fully the dynamic process of cavities development by time-resolved images from fern cavity formation to fissure cavities and then their development to the sheet and strings cavities at finally their collapse.…”
Section: Introductionmentioning
confidence: 99%